2005
DOI: 10.1681/asn.2004121059
|View full text |Cite
|
Sign up to set email alerts
|

Race and Electronically Measured Adherence to Immunosuppressive Medications after Deceased Donor Renal Transplantation

Abstract: Nonadherence to immunosuppressive medications may partly explain the worse allograft outcomes among black recipients of renal transplants. In a prospective cohort study of recipients of deceased donor renal transplants, microelectronic cap monitors were placed on bottles of one immunosuppressive medication to (1) measure average daily percentage adherence during the first posttransplantation year and (2) determine the factors associated with adherence. A total of 278 transplant recipients who provided sufficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
149
3
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(166 citation statements)
references
References 41 publications
12
149
3
2
Order By: Relevance
“…[2][3][4][5]18,25,26 Black Americans have lower access to renal transplantation than white Americans, probably because of lower referral rates for transplantation assessment, which may themselves be due to physician attitudes about poor adherence and lower graft success rates among black patients. 17,22,27,28 Numerous studies from the United States also show inferior graft outcomes among black transplant recipients. Data from the United Network for Organ Sharing registry showed that between 1995 and 1999, the 5-yr graft survival rates for deceased donor transplants was 70 and 55%, respectively, for white and black patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5]18,25,26 Black Americans have lower access to renal transplantation than white Americans, probably because of lower referral rates for transplantation assessment, which may themselves be due to physician attitudes about poor adherence and lower graft success rates among black patients. 17,22,27,28 Numerous studies from the United States also show inferior graft outcomes among black transplant recipients. Data from the United Network for Organ Sharing registry showed that between 1995 and 1999, the 5-yr graft survival rates for deceased donor transplants was 70 and 55%, respectively, for white and black patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, renal allograft survival is significantly lower in black than in white patients, [5][6][7][8][9][10] which might be due to higher immunologic risk, poorer medication adherence, or decreased access to pre-and posttransplantation care. 8,[11][12][13][14][15][16][17][18][19][20][21][22][23] Whether black Canadian transplant recipients also have decreased transplant survival is unclear because there are no published data describing transplant outcomes among this patient group. A recent study comparing outcomes in Canada and the United States demonstrated that American transplant recipients had an increased risk for mortality.…”
mentioning
confidence: 99%
“…30 The effects of transplant center on early and late allograft outcomes have been documented in the United States, Canada, England, and Ireland, [31][32][33][34][35] and adherence with immunosuppressants is associated with the transplant center. 36 Our study is the first to study the transplant center effect using common-donor recipients who underwent transplantation at the same and at different centers. Here, we showed that the within-pair odds for DGF were influenced by the transplant center.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in medication adherence by race-ethnicity exist and have been noted in several studies (2,(5)(6)(7)(8). This may be the result of external factors, such as income, possession of commercial health insurance (5), psychosocial stressors (e.g., residential crime rates) (2,9), and characteristics of the facility where care is provided (6).…”
mentioning
confidence: 99%